Duelling networks: relational clientelism in electoral-authoritarian Malaysia. Issue 1 (2nd January 2020) - Weiss, Meredith L.
ABSTRACT: Malaysia's May 2018 elections saw the ignominious defeat of the long-dominant Barisan Nasional (National Front, BN) coalition at the hands of the alternative Pakatan Harapan (Alliance of Hope, Pakatan). Bolstered by communal sentiments, habit, and charisma, the BN also relied heavily on deeply penetrating clientelist networks and carefully pitched patronage. Opposition parties have long decried the BN's trading of infrastructure, projects, and payments for votes. Yet as these parties have gained greater power themselves, voter expectations have pressed them to rely on similar modes of cultivating support. Whereas diminished access to patronage resources has imperilled dominant parties elsewhere, Malaysia demonstrates a different dynamic. Here, long-term competitive electoral authoritarianism had fostered the emergence of duelling systems of enduring, well-nurtured clientelist ties, despite vastly unequal access to public resources. The demonstration effect of Pakatan performance, including sustained outreach and distributions in states it won substantially via programmatic appeals, reinforced its standing. This "relational clientelism" perversely both helped sustain the BN over decades and reassured voters that they could also rely on Pakatan. I consider Malaysia's intriguing relational clientelism in terms of networks, resources, and discretionary control over those resources, to assess the effects of these practices for electoral outcomes and governance.